Living Hadis : Studi atas Tradisi Sedekah Nasi Bungkus Hari Jumat oleh Komunitas Sijum Amuntai - Muhammad Rafi (Jurnal Living Hadis, 2019)
Poverty is one of the most complex and very significant social problems in influencing social-community settings. Islam through the Qur'an and Sunnah has provided a solution to overcome this poverty problem with the concept of alms. Alms itself is not limited to only assets or material, but can also be done through physical effort, one of which is good deeds to others. There are many verses of the Qur'an and matan hadith that invite Muslims to give alms, either openly or secretly. Then, the text is understood and actualized by Muslims with various kinds of understanding and forms of implementation. This is what later referred to as the hadith living. Living hadith is a sunnah of the Prophet which is freely interpreted by ulama, rulers, judges and Muslims according to the situation, place and conditions they face, or also referred to as "living sunnah". There are three models of hadith living namely writing traditions, oral traditions and traditions of practice. This paper takes the focus of the living of oral hadith that comes along with the practices carried out by Muslims. In this study we will discuss the living of hadith which refers to the tradition of religious practice, more precisely about the understanding of the Sijum community regarding almsgiving and how it is implemented in the tradition of alms rice on Friday for the Sijum Amuntai community. This research is descriptive, qualitative, inductive which means that a study is conducted to get a general description or description of the hadith living. The approach used in this study is a phenomenological approach with functional theory.